Growth and survival of milkfish (Chanos chanos Forsskal) fry in combination with prawn (Penaeus monodon, Fabricius) fry at varying stocking ratio in brackishwater nursery pond - Mesa, Romeo C. (College of Fisheries, U. P. in the Visayas, 1986)
Growth and survival of milkfish fry stocked singly or in combination with prawn (Penaeus monodon, Fabricicus) fry at varying stocking ratios were studied using twelve 144 sq. m. earthen nursery ponds at SEAFDEC Leganes Research Station, Leganes, Iloilo. Four treatments namely Treatment I (all milkfish), Treatment II (2:1) milkfish to prawn) Treatment III (3:1) and Treatment IV (5:1) were tested in a Completely Randomized Design with three replicates. Highest growth of milkfish fry, measured in terms of mean gain in weight was obtained in Treatment II with mean gain in weight of 2.63 g after 45 days of culture, followed by Treatment III with mean gain in weight of 2.00 g. Treatment IV gave lower gain in weight of 1.81 than Treatment I, 1.85 g. Similarly, highest percent survival of 89.5% was obtained in Treatment II. Treatments IV, III and I gave almost the same survival of 85.9, 85.8 and 85.2% respectively. On the other hand, mean gain in weight of P. monodon fry was highest in Treatment III with a value of 1.13 g followed by Treatment IV, 1.05 g. Treatment II gave the lowest mean gain in weight of 0.96 g. Statistical analysis, however, showed no significant differences in growth and percent survival among treatments. Physico-chemical parameters of the pond soil and water measured in all treatments during the 45 days culture period were within the critical values for milkfish and prawn fry culture. Gross community productivity for all treatments had the same trend and were not significantly different. Based on the results of this study the economic analysis showed that Treatment II (2:1 ratio of milkfish to prawn) is the most profitable stocking ratio. This treatment gave a net profit of Php 3,585.10 with a cost-benefit ratio of 1.76.